The Relationship Between Energy Consumption and Economic Growth: Evidence From A Structural Break Analysis For Turkey - Saatci, Mustafa; Dumrul, Yasemin (International Journal of Energy Economics and Policy, 2012)
In this study the aim was to investigate empirically the role of energy consumption in economic growth for the Turkish economy. The data used include annual energy consumption and economic growth series from 1960 to 2008. We used aggregate as well as various disaggregate data on energy consumption, including, oil, electricity, coal and renewable energy. Our contribution is that we take a structural breaks modeling approach in this paper. In the literature, the Kejriwal cointegration test has not been applied to date. The main conclusion of the study was that Turkey’s energy consumption and economic growth has a positive relationship varying quantity with structural breaks. Keywords: Energy Consumption; Economic Growth; Cointegration with Structural Breaks; Turkey. JEL Classifications: C22; O13; Q43